"El manejo de las Relaciones Públicas en la EP-EMAPAR y su incidencia en el desarrollo Institucional, noviembre 2011 abril 2012". - Merizalde Salas, Verónica Elizabeth (2016)
The research topic “The Management of Public Relations in EP-EMAPAR and its Impact on Institutional Development April 2011 November 2012”, is described by one of the major weaknesses that currently the company, which is the absence of a Foreign Policy Public Relations and Communication, on one hand, allow speech align the company to its business objectives and, on the other, make the necessary links with their key audiences to ensure its viability in an increasingly dynamic and complex, the general objective of this work was Determine the management of Public Relations at the EP-EMAPAR and Institutional development impact of the company?, is paper seeks to diagnose the current situation. The importance of internal communication within the institution that plays an essential role, since it is a set of techniques and activities to facilitate and expedite the flow of messages between the members of the institution and influence the opinions, attitudes and conducts internal audiences. Against this, communication becomes one of the key elements within the EP-EMAPAR, because we will maintain a dialogue between equals and come with a clear message to what will work within their tools to enable us to execute our goals. The methodology used was the deductive method could establish particular facts were described, through the application of surveys to staff working in the EP-EMAPAR, for their thoughts on public relations and internal communication, the results were satisfactory, because possible to test the hypothesis and present the conclusions and recommendations.